Development of a research agenda for general practice based on knowledge gaps identified in Dutch guidelines and input from 48 stakeholders. (2nd January 2019) - Burgers, Jako S.; Wittenberg, Jolanda; Keuken, Debby G.; Dekker, Frans; Hohmann, Femke P.; Leereveld, Dieuwke; Ligthart, Suzanne A.; Mulder, Jan-Willem A.; Rutten, Guy; van der Wouden, Johannes C.; van Balen, Jacintha A. M.; Knottnerus, J. André
Abstract: Background: Several funding organizations using different agendas support research in general practice. Topic selection and prioritization are often not coordinated, which may lead to duplication and research waste. Objectives: To develop systematically a national research agenda for general practice involving general practitioners, researchers, patients and other relevant stakeholders in healthcare. Methods: We reviewed knowledge gaps from 90 Dutch general practice guidelines and formulated research questions based on these gaps. In addition, we asked 96 healthcare stakeholders to add research questions relevant for general practice. All research questions were prioritized by practising general practitioners in an online survey ( n  = 232) and by participants of an invitational conference including general practitioners ( n  = 48) and representatives of other stakeholders in healthcare ( n  = 16), e.g. patient organizations and medical specialists. Results: We identified 787 research questions. These were categorized in two ways: according to the chapters of the International Classification for Primary Care (ICPC) and in 12 themes such as common conditions, person-centred care and patient education, collaboration and organization of care. The prioritizing procedure resulted in top 10 lists of research questions for each ICPC chapter and each theme. Conclusion: The process resulted in a widely supported National Research Agenda for General Practice. We encourage both researchers and funding organizations to use this agenda to focus their research on the most relevant issues in general practice and to generate new evidence for the next generation of guidelines and the future of general practice.